Simultaneous determination of benzene, toluene, ethylbenzene, and xylene metabolites in human urine using electromembrane extraction combined with liquid chromatography and tandem mass spectrometry. Issue 24 (24th November 2015) - Suh, Joon Hyuk; Lee, Hye Yeon; Kim, Unyong; Eom, Han Young; Kim, Junghyun; Cho, Hyun‐Deok; Han, Sang Beom
Abstract : For the first time, electromembrane extraction combined with liquid chromatography and tandem mass spectrometry was applied for the determination of urinary benzene, toluene, ethylbenzene, and xylene metabolites. S ‐Phenylmercapturic acid, hippuric acid, phenylglyoxylic acid, and methylhippuric acid isomers were extracted from human urine through a supported liquid membrane consisting of 1‐octanol into an alkaline acceptor solution filling the inside of a hollow fiber by application of an electric field. Various extraction factors were investigated and optimized using response surface methodology, the statistical method. The optimum conditions were established to be 300 V applied voltage, 15 min extraction time, 1500 rpm stirring speed, and 5 mM ammonium acetate (pH 10.2) acceptor solution. The method was validated with respect to selectivity, linearity, accuracy, precision, limit of detection, limit of quantification, recovery, and reproducibility. The results showed good linearity ( r 2 > 0.995), precision, and accuracy. The extract recoveries were 52.8–79.0%. Finally, we applied this method to real samples and successfully measured benzene, toluene, ethylbenzene, and xylene metabolites.